1978
DOI: 10.1042/cs0540147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Immunoreactive Angiotensin in Canine Cerebrospinal Fluid as Des-Asp1-Angiotensin II

Abstract: 1. Immunoreactive angiotensin II was measured in cerebrospinal fluid of four normal dogs. 2. The migration of this immunoreactive angiotensin II on polyacrylamide-slab gel electrophoresis was identical with the migration of the heptapeptide, Des-Asp1-angiotensin II, in each case. 3. The biological activity of the material from canine cerebrospinal fluid in a pressor bioassay was similar to that of Des-Asp1-angiotensin II. 4. The pressor activity of the canine material was abolished by treating the pressor bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…80 However when angiotensin III was added to dog CSF and incubated at 37°C, the levels as measured by radioimmunoassay were altered little over 4 hours and in some instances up to 24 hours. These findings are in agreement with those of Hutchinson et al, 19 who also observed minimal angiotensinase activity in the CSF of dogs. Third, it is conceivable that sodium pentobarbital anesthesia slowed or otherwise altered CSF production or circulation so that angiotensin levels within the cerebral ventricles were not accurately reflected by cisternal sampling.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…80 However when angiotensin III was added to dog CSF and incubated at 37°C, the levels as measured by radioimmunoassay were altered little over 4 hours and in some instances up to 24 hours. These findings are in agreement with those of Hutchinson et al, 19 who also observed minimal angiotensinase activity in the CSF of dogs. Third, it is conceivable that sodium pentobarbital anesthesia slowed or otherwise altered CSF production or circulation so that angiotensin levels within the cerebral ventricles were not accurately reflected by cisternal sampling.…”
Section: Discussionsupporting
confidence: 83%
“…It is pertinent to note that the radioimmunoassay used in these studies utilized an antibody raised against angiotensin II but which cross-reacted 100% with the heptapeptide angiotensin III; therefore, the observations in CSF are valid whichever of the two peptides is the important end product of this renin-angiotensin system. 19 It appears from the above data that immunoreactive angiotensin II levels in CSF and plasma have separate regulatory systems. However, there are a number of other possible explanations or interpretations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting in this respect that angiotensin 111, an intermediate of this metabolic pathway as outlined above, exerts pronounced biological activity in the brain [S]. The functioning of this pathway in vivo is supported by the fact that part of the angiotensin I1 immunoreactivity in canine cerebrospinal fluid [38] and in rat brain tissue [39] has been identified as angiotensin 111. Removal of C-terminal phenylalanine from angiotensin 11, as occurred at the acidic pH, is the most efficient route to rapid inactivation of the peptide, as this removal is accompanied by a dramatic fall in receptor binding and a loss of biological activity.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have revealed the presence of angiotensinogen, isorenin, angiotensin I (ANG I), ANG I converting enzyme and ANG II in the brain or in the cerebrospinal fluid in a number of mammalian species (Ganten et al, 1971;Yang and Neff, 1972;Slavin, 1975;Reid, 1977;Ganten and Speck, 1978;Inagami et al, 1978). The presence of angiotensin III (ANG III) in the cerebrospinal fluid has also been described (Hutchinson et al, 1978). It is well known that injection of ANG II directly into the brain ventricles produces an increase in arterial blood pressure (Smookler et al, 1966;Severs, 1976).…”
Section: Synopsismentioning
confidence: 99%